When an Auto Industry Disappears: Australia's Experience and Lessons for Canada - Stanford, Jim (Canadian Public Policy, 2017)
All three global automakers currently manufacturing vehicles in Australia have announced their total shutdown of operations there by 2017. This shutdown has sparked some fears that Canadian auto manufacturing may follow a similar trajectory. This article reviews the factors contributing to the closures in Australia and considers key structural, economic, and policy differences between the Australian and Canadian cases. The Canadian industry enjoys several structural advantages compared with Australia, chief among them its large and bilateral trade relationship with the United States. These advantages suggest that the Canadian industry has a better prognosis.